Water resource vulnerability assessment in Rawalpindi and Islamabad, Pakistan using Analytic Hierarchy Process (AHP) - Rabia Shabbir; Sheikh Saeed Ahmad (Journal of King Saud University: Science, 2016)
The vulnerability evaluation is always an initial step toward sustainable development. Therefore, the regionalization of the assessment to rationally utilize and develop water resources and planning for the amelioration of the vulnerability status is very important and has practical significance. The present study was aimed to analyze the vulnerability status of the water resource system in Rawalpindi and Islamabad with the help of Analytic Hierarchy Process (AHP) keeping in view the complex, integrated, comprehensive and hierarchical nature of vulnerability evaluation of water resources. The vulnerability index developed as a combination of climatic and socio-economic factors selected on the basis of their significance, relevance and scientific credibility. The water resources in both areas were found relatively vulnerable with the socio-economic factors enhancing the effect of climatic factors. The vulnerability of water resources is of special significance and needs a lot of attention of researchers and policy makers.